2023
DOI: 10.3390/ijms24097821
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Supplements and Over-the-Counter Products to Improve Sleep in Children: A Systematic Review

Abstract: The sleep–wake cycle is a complex multifactorial process involving several neurotransmitters, including acetylcholine, norepinephrine, serotonin, histamine, dopamine, orexin and GABA, that can be, in turn, regulated by different nutrients involved in their metabolic pathways. Although good sleep quality in children has been proven to be a key factor for optimal cognitive, physical and psychological development, a significant and ever-increasing percentage of the pediatric population suffers from sleep disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…L-theanine is an amino acid found in green tea leaves, Camellia sinensis, and is thought to alleviate stress and improve sleep through a glutamate receptor-mediated mechanism (Lyon et al, 2011;Innocenti et al, 2023). One randomized, 10-week, doubleblind, placebo-controlled trial conducted with 98 boys, ages 8-12 years, with a diagnosis of ADHD observed improved sleep efficiency as measured by actigraphy but no change in sleep latency or duration at doses of 200 mg twice daily.…”
Section: L-theaninementioning
confidence: 99%
“…L-theanine is an amino acid found in green tea leaves, Camellia sinensis, and is thought to alleviate stress and improve sleep through a glutamate receptor-mediated mechanism (Lyon et al, 2011;Innocenti et al, 2023). One randomized, 10-week, doubleblind, placebo-controlled trial conducted with 98 boys, ages 8-12 years, with a diagnosis of ADHD observed improved sleep efficiency as measured by actigraphy but no change in sleep latency or duration at doses of 200 mg twice daily.…”
Section: L-theaninementioning
confidence: 99%